Characterization and deslignication of Dictyota dichotoma - Fdez.-Ladreda, Ignacio Tomé; Moral Rama, Ana; Ballesteros Martin, Maria de la Menta (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2016)
Motivation: Algae, with more than 27,000 species, includes a great variety of aquatic organisms with a high ecological importance. Every yearthousands tons of sea waste are acumulated on the shore. Consequently some investigations are recently focused on its potential as raw material for animal food, bioethanol or cellulose extraction among others. Currently there are not many studies about the use of these wastes for cellulose extraction. The objetive of this project is to characterize the algae Dictyota dichotoma.and compare two different deslignification treatments. Methods: The characterization of the specie Dictyota dichotoma, seaweed was carried out, in order to determinate the composition of benzene ethanol extractables, ashes, hot water solubility, lignin, holocellulose and alfa-cellulose. On the other hand, the diference between two chemical treataments for the delignification of D. dichotoma was studied using NaOH, antraqinone and H2O2 or NaCl2O. Also an experimental designwas carried out taking into account the effect of five independent variables( time, temperature, antraqinone, NaOH and H2O2 or NaCl2O) on whiteness.. Results: The obtained results allow to conclude that Dictyota dichotoma presents a low content in lignin, with 16.07%. Conclusions: The study demonstrates that D.dichotoma is an adequate alternative as raw material for papermaking due to its low content of lignin (16%)in comparison with other vegetables terrestrial species which facilitates cellulose extraction. Moreover this algae present elevate contents in cellulose (34,8% of holocollulose and 30,6% of alpha-cellulose) and its extraction can be carried out using clean technologies.